Nutrition Therapy Management in a Client with Obesity Grade III and Gastroesophageal Reflux Disease (GERD) - Andara, Fathiya; Noer, Etika Ratna (Ikatan Sarjana Gizi Indonesia (ISAGI), 2025)
Obesity and gastroesophageal reflux disease (GERD) are interrelated conditions that can exacerbate each other, requiring comprehensive and individualized nutritional management. This case report aims to describe the implementation of targeted nutrition therapy in a client with Obesity Grade III and a history of GERD through an approach focused on moderate energy deficit, balanced macronutrient composition, and gradual physical activity improvement. The 14-day intervention included daily monitoring to assess dietary changes, nutritional status, and digestive symptoms. The results demonstrated improved dietary patterns, weight reduction, and enhanced digestive comfort, highlighting the strong relationship between nutritional regulation and GERD symptom control. This case underscores that consistent lifestyle modification, through dietary adjustment and increased physical activity can positively impact nutritional status and quality of life. Such individualized nutrition approaches may serve as practical and evidence-based strategies in managing obesity with comorbid GERD